Kelenteng Kong Fuk Nio dan Masjid Jami Muntok dalam Worldview Toleransi Kota Muntok - Primayudha, Novrizal; Santosa, Imam; Syarief, Achmad; Destiarmand, Achmad Haldani (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The long history of ethnic and religious tolerance in Indonesia has always tended to tell a story about expressions of indifference, and even hidden persuasiveness, which scrutinizes the problems of large organizations such as religion and culture. By concentrating on two contiguous places of worship of two religious’ communities in Muntok City, West Bangka, this article strives to identification from a side that is rarely exposed. The observation, interviews, and the acquisition of literature data elucidate how the application of amalgamated components in the two places of worship is a product of tolerance practices negotiated in the past hence it is of utmost significance to refrain from disregarding this historical substance through the interpretation of anomalous forms or idealized occasionalism. Thus, through Rainer Forst's concept of